REAL ESTATE MARKET: CONCEPTUAL FRAMEWORK - Han, Nazli (YILDIZ TECHNICAL UNIV, 2012)
Real Estate market and real estate development process provide significant data for understanding the formation of built environment and the urban processes. All the same, for a long period of time it was evaluated as the background in which urban relations take place and was also assumed to be relatively passive. The economical structure that has been changing since 80's, in relation with the real estate market, gave rise to important transformation in cities. From then on, focus on the subject accelerated. It can be observed that in terms of literature there are three main approaches evaluating the issue. While neo-classical approach identifies the real estate from the perspective of supply& demand, political economy approach interprets the issue in the context of the flow of capital to constructed area during the capital accumulation process and lastly institutionalist approach by evaluating the more concrete, concentrates on the instutions shaping the process.
Keywords: Real estate market; development process; theoretical approach; GROUND RENT; PROPERTY; INVESTMENT; CIRCUITS; LAND; Engineering